Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Díaz Valencia, Andrea Hilda (2019)
Camposol is a Peruvian company that develops in the agricultural sector and markets products such as fruits, vegetables and seafood since 1997. However, in recent years it has undergone major changes due to global consumer trends and has had to use different strategies to adapt and maintain its competitive strategy in the market based on innovation and guaranteed quality in its products, maintaining synergy and constant communication in the activities of the value chain and develop a vertical integration model.